UGT76B1, a promiscuous hub of small molecule-based immune signaling, glucosylates N-hydroxypipecolic acid, and balances plant immunity. Issue 3 (13th January 2021) - Bauer, Sibylle; Mekonnen, Dereje W; Hartmann, Michael; Yildiz, Ipek; Janowski, Robert; Lange, Birgit; Geist, Birgit; Zeier, Jürgen; Schäffner, Anton R
Abstract : The parallel ability of the Arabidopsis glucosyltransferase UGT76B1 to conjugate and inactivate three signaling compounds mutually balances their activity and limits the immune response. Abstract: Glucosylation modulates the biological activity of small molecules and frequently leads to their inactivation. The Arabidopsis thaliana glucosyltransferase UGT76B1 is involved in conjugating the stress hormone salicylic acid (SA) as well as isoleucic acid (ILA). Here, we show that UGT76B1 also glucosylates N-hydroxypipecolic acid (NHP), which is synthesized by FLAVIN-DEPENDENT MONOOXYGENASE 1 (FMO1) and activates systemic acquired resistance (SAR). Upon pathogen attack, Arabidopsis leaves generate two distinct NHP hexose conjugates, NHP-O-β-glucoside and NHP glucose ester, whereupon only NHP- O -β-glucoside formation requires a functional SA pathway. The ugt76b1 mutants specifically fail to generate the NHP- O -β-glucoside, and recombinant UGT76B1 synthesizes NHP- O -β-glucoside in vitro in competition with SA and ILA. The loss of UGT76B1 elevates the endogenous levels of NHP, SA, and ILA and establishes a constitutive SAR-like immune status. Introgression of the fmo1 mutant lacking NHP biosynthesis into the ugt76b1 background abolishes this SAR-like resistance. Moreover, overexpression of UGT76B1 in Arabidopsis shifts the NHP and SA pools toward O -β-glucoside formation and abrogates pathogen-induced SAR. Our results further indicate that NHP-triggered immunity is SA-dependent and relies on UGT76B1 as a common metabolic hub. Thereby, UGT76B1-mediated glucosylation controls the levels of active NHP, SA, and ILA in concert to balance the plant immune status.